Virtual reality as a tool for graphic presentation in architectural education (2006)
This paper critically appraises the use of virtual reality software packages in the design and modelling of built environment in Nigeria, such as Studio Max, 3D Studio, AutoCAD, ArchiCAD. Approaches involving the use of VR design packages to model historic buildings in the Nigerian Urban centers, with the use packages to model historic buildings in the Nigerian Urban centers, with the use of walkthrough, animination and real time studio work. The paper showcase recent research work which include new development that allow for the client or end users to be part of the design process. Illustrations, sample drawings and photographs of building s both existing and proposed are copiously